Evaluation of Split Root Nutrient Film Technique (SR-NFT) for Yield and Tipburn of Hydroponically Grown Lettuce (Lactuca sativa L.) Under Differing Nutrient Concentrations - Yuta Inoue; Nicholas S. Kaczmar; Chito F. Sace; John Osborn; Neil S. Mattson (Agriculture, 2025)
Previous research has shown the benefits of splitting nutrient application to plant roots either temporally or spatially. A split-root nutrient film technique (SR-NFT) was developed for lettuce where an NFT channel is divided longitudinally into two separate channels, each with its own input and drain line. In this system, plant roots can be intentionally divided to supply different nutrient solutions without mixing them. Plant growth was observed using combinations of three different hydroponic fertilizer concentrations: EC 0.5 dS∙m−1 (L, tap water), EC 1.8 dS∙m−1 (M, nutrient solution), and EC 3.1 dS∙m−1 (H, nutrient solution). For the same average concentration of solution (EC 1.8 dS∙m-1), SR-NFT that supplied different concentrations of solution on the left and right side (SHL, Left; EC 0.5 dS∙m−1, Right; EC 3.1 dS∙m−1) increased the shoot fresh and dry weight by 15%, shoot dry weight by 14%, and root dry weight by 25% without increasing number of tipburn leaves compared to conventional NFT (MM, EC 1.8 dS∙m−1). In addition, the lowest concentration with SR-NFT (SML, Left; EC 1.8 dS∙m−1, Right; EC 0.5 dS∙m−1) reduced the number of tipburn leaves without reducing the shoot fresh weight in all conditions except SMM (Left; EC 1.8 dS∙m−1, Right; EC 1.8 dS∙m−1). In other words, the use of tap water on one side is expected to suppress tipburn or increase yield.